Umumu'l-Musterek in Literature of Usul al-Fiqh - Karatas, Fatih (Şırnak Univ, 2020)
The way to understand and make sense of the nass (divine decrees) soundly is examined in the section called istinbat (rational inference) methods in the classical works of fiqh (Islamic jurisprudence). In this section, one of the words that we encounter in divine decrees, musterek is also discussed. The term musterek, which has more than one meaning and has been imposed for each meaning, was used in divine decrees of the Book and Sunnah. The issue of which meaning of musterek is intended by Sari has been a reason for the disputes between scholars of usul al-fiqh (Islamic practice). Furthermore, the issue of umumu'l-musterek has been one of the most prominent discussions about musterek. The issue in question, which we can briefly explain that whether it is possible to address all of the meanings of musterek imposed, is one of the important debate topics among the scholars of usul al-fiqh. The explanation of the concept in the works of usul, the controversial views on it, the evidence, and the famous examples related to the subject are the issues discussed in this study. Besides, some examples that are mentioned in classical usul al-fiqh works but considered to be nonrelevant for the subject will also be criticized. In this study, it is aimed to clarify the nature of the aforementioned concept, to reveal that some examples in classical works are not relevant to the subject, and finally choose one of the controversial views on the subject. Thus, the topic of umumu'l-musterek, one of the important causes of conflict in subsidiary (fer'i) jurisprudence matters and one of the basic concepts of usul al-fiqh and its impossibility will be clarified by presenting the subject systematically.
Keywords: Fiqh; Usul al-Fiqh; Imposition; Musterek; Umum'l-musterek; Spiritual Musterek